Functional characterization of the C-terminal domain of the cytochrome c maturation protein CcmE. - Harvat, E; Stevens, J; Redfield, C; Ferguson, S (2005)
CcmE is a heme chaperone involved in the periplasmic maturation of c-type cytochromes in many bacteria and plant mitochondria. It binds heme covalently and subsequently transfers it to the apo form of cytochromes c. To examine the role of the C-terminal domain of CcmE in the binding of heme, in vitro heme binding to the apo form of a truncated (immediately before Pro-136) version of the periplasmic domain of the heme chaperone from Escherichia coli was studied. Removal of the C-terminal domain dramatically altered the ligation of non-covalently bound heme in CcmE' (the soluble form lacking the membrane anchor) but only slightly affected its affinity for protoporphyrin IX and 8-anilino-1-naphthalenesulfonate. This finding has significant mechanistic implications for in vivo holo-CcmE formation and indicates that the C-terminal region is not required for the recruitment and docking of heme into its binding site but is likely to contain amino acid(s) involved in heme iron axial coordination. Removal of the C-domain significantly impaired in vivo heme binding to CcmE and conversion of apocytochrome to holoprotein by a similar factor, suggesting that the C-terminal domain of the chaperone is primarily involved in heme binding to CcmE rather than in heme transfer to the apo cytochrome.